Combined Double-Segment Spinal-Epidural Anesthesia With Fixation of the Epidural Catheter in the Subcutaneous Canal Using a Modified Spinal Needle - D. N. Protsenko; O. N. Yamshikov; A. P. Marchenko; S. A. Yemelyanov; R. A. Marchenko; E. A. Kolobova (Неотложная медицинская помощь)
Aim of study To develop a new safe and reliable method of fixing an epidural catheter (EC), to study and compare the results of this method of fixing EC in the subcutaneous canal using a modified spinal needle (MSN) and an adhesive tape with a standard method of fixing an EC using only an adhesive tape when performing the combined double-segment spinal-epidural anesthesia (CDSEA) in the surgical treatment of fractures of the bones of the lower limb.Material and methods A comparative study of two methods of EC fixation was carried out in patients undergoing CDSEA during the surgical treatment of fractures of the bones of the lower limb. The patients were divided into two groups. The Group 1 (comparison, n=65), where EC was fixed at the site of epidural access with adhesive tape and the Group 2 (study, n=65), where EC was fixed in the subcutaneous canal using MSN and adhesive tape at the site of EC exit on the skin.Results In the study group, where EC was fixed in the subcutaneous canal using MSN and adhesive tape at the site of EC exit to the skin, there were 32.3% fewer cases with clinically significant dislocation (more than 15 to 30 mm) than in the comparison group, where EC was fixed at the site of epidural access only with adhesive tape.Conclusions A used spinal needle in a modified version can be used to perform EC in the subcutaneous canal. The dimensions of the MSN allow tunneling of the EC less traumatic and at a great distance from the site of the epidural access, which provides more reliable fixation of the EC, the number of cases with clinically significant + dislocation decreases, this allows for a longer and better postoperative epidural analgesia. This method does not solve all the problems of EC fixation; it is required to develop new methods of EC fixation, including fixation in the subcutaneous canal.